Investigating the Impact of Language On E-Learning Quality Using SERVQUAL Model - Dr. M. Amaad Uppal , Dr. Samnan Ali, Zunaira Zahid, Muhammad Basir (International Journal of Advanced Science and Technology, 2020)
In the recent past, adoption of electronic learning (e-learning) has widely grown as a promising solution for higher education sector. E-learning, also known as digital learning, virtual learning, technology enhanced learning, has many benefits including time and space flexibility which results in cost saving and making learning opportunities available to a wider population. This trend of learning through latest digital technologies has also received a lot of attention from researchers and ample research exists which focuses on e-learning benefits and challenges. However, education is a service, and quality of service is a key indicator to assess any service, very limited research has been conducted to assess quality related issues of e-learning systems in an educational context. In our paper, we recommend use of SERVQUAL model, which has been widely accepted as a reliable model for perception of service quality assessment to assess the quality of e-learning. This model is comprised of five constructs: Assurance, Reliability, Empathy, Responsiveness and Web-site content. Additionally, “Language” is introduced as a moderator to study its impact on the overall model. Language has been used as a moderator since learning content is the key in any education environment, and medium of language is the central element within the curriculum. Reliability and validity of measurement model has been analyzed through Structured Equation Modeling. Analysis from a sample of 300 students reveals that the overall satisfaction of e-learning is enhanced when delivery is done using local language. This is evident from the enhanced values on “Empathy” and “Website Content” dimensions.